Experimental study on an injection-assisted air source heat pump with a novel two-stage variable-speed scroll compressor. (25th July 2020) - Wang, Jijin; Qv, Dehu; Ni, Long; Yao, Yang
Highlights: A novel two-stage variable-speed scroll compressor is introduced. Effects of gas injection & compressor frequency on heating performance are studied. The discharge temperature of IDCAHP is reduced by at least 40.0 °C. Falling intermediate pressure improves COP of R22 heat pump used scroll compressor. Abstract: Traditional air source heat pumps (ASHPs) with scroll compressors were limited in terms of variable volume ratio. An injection-assisted ASHP using a novel two-stage variable-speed scroll compressor with a variable volume ratio and direct current (DC) speed regulation motor, named IDCAHP, was proposed herein for improving heating performance in cold and/or severely cold regions over wide-range temperature conditions. Experiments focusing on the IDCAHP heating performance under different temperatures and various characteristics of the compressor frequency were performed. Results indicated that the IDCAHP performed well over wide-range temperature conditions. In particular, the discharge pressure decreased steadily with falling ambient temperature, and the discharge temperature of the IDCAHP increased with the rising pressure ratio by less than 82.6 °C at an ambient temperature of −20.0 °C. Additionally, gas injection and increasing the compressor frequency could improve the heating capacity of the IDCAHP. As the ambient temperature was −20.0 °C, the heating capacity reached 68.1% of the nominal condition, and the heating coefficient of performance ( COP ) and energy efficiency ratio ( EER ) of the IDCAHP could reach 2.0 and 1.8, respectively. Moreover, the decreasing intermediate pressure improved the heating performance. By contrast, with a common ASHP without gas injection, quasi-two-stage compression air-source heat pump with an economiser (QCAHP-E), quasi-two-stage compression air-source heat pump with a flash tank (QCAHP-F), and two-stage compression air-source heat pump (TCAHP) system, the COP of the IDCAHP increased to 35.0%, 4.2%, 37.6%, and 16.2%, respectively, whereas the discharge temperature decreased to 47.9 °C, 46.5 °C, 62.7 °C, and 40.7 °C, respectively.